The Kumaraswamy compound Rayleigh distribution : properties and estimation - Reyad, Hesham; Othman, Soha A.; Younis, Adil M; Hashish, Ahmed M. (International Journal of Advanced Mathematical Sciences, 2017)
We introduce a new four parameter continuous model, called the Kumaraswamy compound Rayleigh (KwCR) distribution that extends the compound Rayleigh distribution. We study some mathematical properties of this distribution such as; mean, variance, coefficient of variation, quantile function, median, ordinary and incomplete moments, skewness, kurtosis, moment and probability generating functions, reliability analysis, Lorenz, Bonferroni and Zenga curves, Rényi of entropy, order statistics and record statistics. We consider the methods of moments and maximum likelihood for estimating the model parameters.